2018
DOI: 10.1039/c8ra00063h
|View full text |Cite
|
Sign up to set email alerts
|

UV-curable ladder-like diphenylsiloxane-bridged methacryl-phenyl-siloxane for high power LED encapsulation

Abstract: UV-curable ladder-like polysiloxane was constructed to integrate high RI (1.61/450 nm) with high thermal stability etc. for high power LED encapsulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Recently, Hwang et al reported the synthesis of various functional ladder-like structured polysilsesquioxanes (LPSQs) synthesized by the sol–gel reaction with a solvent over ten days and compared the thermal and mechanical properties of the LPSQs with POSS, which have carbazole and phenyl groups [21,22,23]. Hwang et al also reported a hybrid ionogel electrolytes using methacrylate LPSQs for lithium ion batteries, and Zhang et al applied the methacrylate-phenyl LPSQs into LED encapsulation [16,24,25]. Despite of the high potency of LPSQs as optical and electrical application, their application area is still limited and the complicate and time-consuming synthetic process are issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hwang et al reported the synthesis of various functional ladder-like structured polysilsesquioxanes (LPSQs) synthesized by the sol–gel reaction with a solvent over ten days and compared the thermal and mechanical properties of the LPSQs with POSS, which have carbazole and phenyl groups [21,22,23]. Hwang et al also reported a hybrid ionogel electrolytes using methacrylate LPSQs for lithium ion batteries, and Zhang et al applied the methacrylate-phenyl LPSQs into LED encapsulation [16,24,25]. Despite of the high potency of LPSQs as optical and electrical application, their application area is still limited and the complicate and time-consuming synthetic process are issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large difference in the onset temperature of weight loss was not observed. The results indicate that factors that reduce thermal properties of our hybrid materials are due to monomers and unreacted functional groups of PSQ-SH and the hydroxy group (-OH group) at the PSQ-SH terminal (Shang et al, 2018).…”
Section: Thermogravimetry-differential Thermal Analyzer (Tg-dta) Analmentioning
confidence: 95%
“…However, with the highest phenyl substitution, the siloxanes may still subject to a RI ceiling of $1.6. [19][20][21][22] The other way to increase the RI of siloxane is by introducing inorganic nanoparticles with high RI, such as ZrO 2 , TiO 2 , and ZnO into the matrix. The RI of the composite can be varied in a wide range according to the method of preparation and nanoparticle content.…”
Section: Introductionmentioning
confidence: 99%